Which dimensions of nature contact in Urban Green Spaces most significantly contribute to mental wellbeing? A multidimensional analysis in Brazilian metropolitan cities - Bressane, Adriano [UNESP]; da Cunha Pinto, Joao Pedro [UNESP]; Garcia Goulart, Ana Paula [UNESP]; César de Castro Medeiros, Líliam [UNESP] (Elsevier, 2024)
Background: Urban environments pose challenges to mental health, an issue that Urban Green Spaces (UGS) can potentially mitigate. While the benefits of nature contact for mental wellbeing are recognized, a multidimensional analysis remains unexplored. Purpose: This study aims to fill this gap by examining the association between nature contact within UGS and mental health. It underscores the importance of considering multiple dimensions of nature engagement—such as naturalness, intensity, duration, frequency, and infrastructure—in enhancing psychological wellbeing. Method: A comprehensive analysis, including canonical correlation, multivariate analyses of variance, and Fisher discriminant analysis, was applied to survey data from several Brazilian metropolitan cities to assess how different aspects of nature contact influence mental health. Results and conclusions: Findings reveal association between these dimensions and mental wellbeing indicators, highlighting the importance of a multidimensional perspective. Practical implications: Results advocate for incorporating diverse aspects of nature contact in UGS design and policy-making to enhance urban dwellers' mental health. Future directions: Further research should focus on longitudinal studies and explore the mediating effects of socio-demographic factors. Additionally, expanding research to include other developing countries will provide valuable comparative insights.
Keywords: Developing countries; Mental wellbeing; Multidimensional analysis; Nature contact; Urban Green Spaces